The Effects of Green Tea on Weight Loss in Obese Individuals - Pereira, Eric (Université d'Ottawa | University of Ottawa, 2014)
As the rate of obesity has gone up, the use of dietary supplements has also seen a rise in popularity and has been the big rage over the past couple of years as people attempt to discover the secret to easy weight loss. In most dietary supplements found on the market, there are traces of green tea extract due to the perceived health benefits it offers as well as the increased weight loss that is associated with it. For the purpose of this project, we reviewed the literature in order to assess the evidence available to determine whether or not a correlation truly exists between weight loss and the consumption of green tea catechins extract. The literature review was conducted using the University of Ottawa’s library database as well as PubMed, Scopus and Google Scholar. We used the following key words to facilitate the search for relevant peer-reviewed articles: green tea, green tea extract, weight loss, obesity, health and benefits. Throughout the research process we have found evidence that the use of green tea extract supplements and other products formulated with it do, in fact have positive effects on obese individuals whose goals are to increase weight loss, increase fat oxidation, decrease appetite as well as disrupt nutrient absorption within the body. Future research on the subject is still needed,